Crankcase explosion for two-stroke marine diesel engine by using fault tree analysis method in fuzzy environment. (March 2019) - Ünver, Bedir; Gürgen, Samet; Sahin, Bekir; Altın, İsmail
Abstract: The purpose of this study is to investigate crankcase explosion in two-stroke marine diesel engine systematically by using fault tree analysis method in fuzzy environment for system reliability and shipping sustainability. Maritime accidents might cause deadly and costly results in both human lives, commodities, environmental and financial aspects. Crankcase explosion is one of the most dangerous causalities that might possibly damage both ship structure and crew members. In this study, we determine all root causes of crankcase explosion, and calculate the probabilities in a stepwise manner by implementing field expert consultations. As a result, we find that the occurrence probability of the crankcase explosion is 1.249428E-007 which is close to real case. Bearing originated hot spots and personnel failures are also found as the most risky events. Highlights: Root causes and structure of crankcase explosion are investigated in this study. Fuzzy fault tree analysis method is firstly applied to analyze crankcase explosion. The probability of crankcase explosion is found as 1.25E-07. The riskiest event chain is determined as MCS1 (BE11, UE and BE4). Underlying reasons of crankcase explosion are explained, and suggestions are given.